Environmental Care Character Education Based On Local Wisdom For Marine Resource Management - Marlina Marlina; Ramadhani Lausi Mkumbachi; Azmin Mane; Laode Rahman Daud (JAMBURA GEO EDUCATION JOURNAL, 2023)
The character of caring for the environment through local culture is increasingly being encouraged. However, the concept of integrating local culture in forming an environmentally caring character in managing marine resources has not been implemented. Meanwhile, environmental awareness is important to realize good environmental quality. The community must have the character of caring for the environment as a conservation effort, including the concern of the Bajo community in managing the Wakatobi National Park area. The aim of this research is to examine the local wisdom values of the Bajo Mola community in Wakatobi National Park, including the local wisdom of Duata Sangal, Parika and Pamali contained in environmentally caring character education which is integrated through high school geography learning. The research method uses descriptive qualitative with data collection through interviews, observations and literature reviews which are analyzed using model triangulation. The results of the research are that character education that cares about the environment can be developed through the use of marine resources through the local wisdom of the Bajo Mola community. Bajo Mola local wisdom values in class XI Geography learning. Educators can apply it by integrating it into learning material, so that they can form environmentally. Caring characters in students.  As a community with a maritime culture, local wisdom values contain indicators of environmentally caring character that can be integrated into geography learning. Through environmental care character education based on the local wisdom of the Bajo Mola Waakatobi tribe, it is hoped that it can foster an attitude of caring for the environment in society.